Exercise-Induced Oxidative Stress and the Effects of Antioxidant Intake from a Physiological Viewpoint - Takuji Kawamura; Isao Muraoka (MDPI AG, 2018)
It is well established that the increase in reactive oxygen species (ROS) and free radicals production during exercise has both positive and negative physiological effects. Among them, the present review focuses on oxidative stress caused by acute exercise, mainly on evidence in healthy individuals. This review also summarizes findings on the determinants of exercise-induced oxidative stress and sources of free radical production. Moreover, we outline the effects of antioxidant supplementation on exercise-induced oxidative stress, which have been studied extensively. Finally, the following review briefly summarizes future tasks in the field of redox biology of exercise. In principle, this review covers findings for the whole body, and describes human trials and animal experiments separately.